Transgenic resistance to the nematode Rotylenchulus reniformis conferred by Arabidopsis thaliana plants expressing proteinase inhibitors - Urwin, Peter E.; Levesley, Aurora; McPherson, Michael J.; Atkinson, Howard J. (Molecular breeding, 2000)
The level of resistance to the reniform nematode Rotylenchulus reniformis conferred on Arabidopsis thaliana by transgenic expression of proteinase inhibitors (PI) was studied over 40 days of infection. A cysteine PI differing from Oc-I expressed in rice seed by one amino acid (Oc-IΔD86) had a considerable effect. It reduced parasite density and fecundity to 65±4% and 31±8% respectively, relative to values for untransformed plants when expressed at ca. 0.4% total soluble protein. The overall reproductive success was only 19±5% relative to the controls. Similar expression levels of cowpea trypsin inhibitor, a serine PI, reduced the density of the females on the plants to 77±3% of control values but did not reduce their fecundity. There was no evidence for additive effects when both PIs were expressed as a fusion protein using a peptide linker. Both PIs in the fusion PI protein are known to be functional from our previous work. When developing on A. thaliana plants expressing the transgenic proteins the intact PI fusion protein of 22 kDa was detected in nematodes by western blot analysis. Similarly, R. reniformis females were observed to have ingested Green Fluorescent Protein (28 kDa). Demonstrating the ingestion of the fusion protein, which has been associated with additive effects of the two PIs against other nematodes, supports the observation that serine PIs are of less value than cysteine PIs for R. reniformis control. The effect of Oc-IΔD86 on R. reniformis was dependent on the level of expression of different A. thaliana lines in the range of 0.1–0.4% total soluble protein indicating that the upper level of expression is required for an effective defence. Virtual northern analysis with cysteine and serine proteinase gene probes from Heterodera glycines showed high transcript abundance of a serine proteinase in both pre-parasitic and parasitic stages whereas expression of the cysteine proteinase was more abundant in the feeding adult female. This study provides further evidence that cystatins represent a valuable source of control against a range of economic nematodes including Globodera, Heterodera and Meloidogyne and now including R. reniformis. Preliminary screening in A. thaliana provides a convenient guide for selection of transgenes against nematode pathogens of crops such as pineapple that have a prolonged regeneration period.